Impact of COVID-19 related social support service closures on people with dementia and unpaid carers: a qualitative study. (3rd July 2021) - Giebel, Clarissa; Cannon, Jacqueline; Hanna, Kerry; Butchard, Sarah; Eley, Ruth; Gaughan, Anna; Komuravelli, Aravind; Shenton, Justine; Callaghan, Steve; Tetlow, Hilary; Limbert, Stan; Whittington, Rosie; et al.
Abstract: Objectives: Accessing social care and social support services is key to support the well-being of people living with dementia (PLWD) and unpaid carers. COVID-19 has caused sudden closures or radical modifications of these services, and is resulting in prolonged self-isolation. The aim of this study was to explore the effects of COVID-19 related social care and support service changes and closures on the lives of PLWD and unpaid carers. Method: PLWD and unpaid carers were interviewed via telephone in April 2020. Transcripts were analysed using thematic analysis. Demographic characteristics including household Index of Multiple Deprivation score and weekly hours of social support service usage before and since the COVID-19 outbreak were also collected. Paired samples t-tests was used to compare the mean of weekly hours of social support service usage before and since the outbreak. Results: 50 semi-structured interviews were conducted with unpaid carers ( n  = 42) and PLWD ( n  = 8). There was a significant reduction in social support service usage since the outbreak. Thematic analysis identified three overarching themes: (1) Loss of control; (2) Uncertainty; (3) Adapting and having to adapt to the new normal. Carers and PLWD were greatly affected by the sudden removal of social support services, and concerned about when services would re-open. Carers were worried about whether the person they cared for would still be able to re-join social support services. Conclusions: PLWD and carers need to receive specific practical and psychological support during the pandemic to support their well-being, which is severely affected by public health restrictions.